Lingkungan Keluarga Anak-Anak Berprestasi Tinggi dan Anak-Anak Berprestasi Rendah di SMA Negeri Kabupaten Pidie Sigli - Husaini Daud; Cut Sufiati; Zakaria Abdullah; Amrusi Amrusi (Universitas Negeri Malang, 2016)
This study describes the contribution of family environment to the achievement of students. Data were collected from the high achievers and low achievers of SMAN grade II student at Kabupaten Pidie Sigli. The result reveals that 5 sub-variables of family environment do not show significant contribution to the student's achievement, while 6 of them give significant contributions though they are not applicable, and 8 of them are significant and applicable.